Human Brain Expansion during Evolution Is Independent of Fire Control and Cooking - Cornélio, Alianda M.; de Bittencourt-Navarrete, Ruben E.; de Bittencourt Brum, Ricardo; Queiroz, Claudio M.; Costa, Marcos R. (Frontiers in Neuroscience, 2016)
What makes humans unique? This question has fascinated scientists and philosophers for centuries and it is still a matter of intense debate. Nowadays, human brain expansion during evolution has been acknowledged to explain our empowered cognitive capabilities. The drivers for such accelerated expansion remain, however, largely unknown. In this sense, studies have suggested that the cooking of food could be a pre-requisite for the expansion of brain size in early hominins. However, this appealing hypothesis is only supported by a mathematical model suggesting that the increasing number of neurons in the brain would constrain body size among primates due to a limited amount of calories obtained from diets. Here, we show, by using a similar mathematical model, that a tradeoff between body mass and the number of brain neurons imposed by dietary constraints during hominin evolution is unlikely. Instead, the predictable number of neurons in the hominin brain varies much more in function of foraging efficiency than body mass. We also review archeological data to show that the expansion of the brain volume in the hominin lineage is described by a linear function independent of evidence of fire control, and therefore, thermal processing of food does not account for this phenomenon. Finally, we report experiments in mice showing that thermal processing of meat does not increase its caloric availability in mice. Altogether, our data indicate that cooking is neither sufficient nor necessary to explain hominin brain expansion.